Assessing a single-cell multi-omic analytic platform to characterize ex vivo-engineered T-cell therapy products - Moshref, Maryam; Lo, Jerry Hung-Hao; McKay, Andrew; Camperi, Julien; Schroer, Joseph; Ueno, Norikiyo; Wang, Shu; Gulati, Saurabh; Tarighat, Somayeh; Durinck, Steffen; Lee, Ho Young; Chen, Dayue (Frontiers in Bioengineering and Biotechnology, 2024)
Genetically engineered CD8 + T cells are being explored for the treatment of various cancers. Analytical characterization represents a major challenge in the development of genetically engineered cell therapies, especially assessing the potential off-target editing and product heterogeneity. As conventional sequencing techniques only provide information at the bulk level, they are unable to detect off-target CRISPR translocation or editing events occurring in minor cell subpopulations. Here we report the analytical development of a single-cell multi-omic DNA and Protein assay to characterize genetically engineered cell products for safety and genotoxicity assessment. We were able to quantify on-target edits, off-target events, and potential translocations at the targeting loci with per-cell granularity, providing important characterization data of the final cell product.Conclusion: Single cell multi-omics approach provides the resolution required to understand the composition of cellular products and identify critical quality attributes (CQAs).